2016
DOI: 10.1021/acs.jafc.6b02203
|View full text |Cite
|
Sign up to set email alerts
|

Quantitation of Aristolochic Acids in Corn, Wheat Grain, and Soil Samples Collected in Serbia: Identifying a Novel Exposure Pathway in the Etiology of Balkan Endemic Nephropathy

Abstract: While to date investigations provided convincing evidence on the role of aristolochic acids (AAs) in the etiology of Balkan endemic nephropathy (BEN) and upper urothelial cancer (UUC), the exposure pathways by which AAs enter human bodies to cause BEN and UUC remain obscure. The goal of this study is to test the hypothesis that environmental pollution by AAs and root uptake of AAs in the polluted soil may be one of the pathways by which AAs enter the human food chain. The hypothesis driving this study was that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
125
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 68 publications
(128 citation statements)
references
References 35 publications
2
125
1
Order By: Relevance
“…In this regard, they showed that the roots of maize plant and cucumber were capable of absorbing AA confirming the possible involvement of naturally occurring root uptake in food chain contamination. Subsequently, AA were also identified in corn, wheat grain and soil samples collected from the endemic village of Kutles in Serbia providing the first direct evidence that food crops and soil are contaminated with AA in Balkan countries and thereby strengthening the intoxication pathway proposed earlier [60]. Finally, another recent study tested the hypothesis that AA could be translocated and bioaccumulated in food crops to cause chronic dietary poisoning [61].…”
Section: Epidemiology Of Aan and Ben: A True Link?mentioning
confidence: 98%
“…In this regard, they showed that the roots of maize plant and cucumber were capable of absorbing AA confirming the possible involvement of naturally occurring root uptake in food chain contamination. Subsequently, AA were also identified in corn, wheat grain and soil samples collected from the endemic village of Kutles in Serbia providing the first direct evidence that food crops and soil are contaminated with AA in Balkan countries and thereby strengthening the intoxication pathway proposed earlier [60]. Finally, another recent study tested the hypothesis that AA could be translocated and bioaccumulated in food crops to cause chronic dietary poisoning [61].…”
Section: Epidemiology Of Aan and Ben: A True Link?mentioning
confidence: 98%
“…The mixture was then subjected to ultrasonication at 50°C for 1 h to extract AAs from the soil. Following centrifugation at 6000 g for 10 min, 1 mL of the sample extract was reacted with 20 mg of pre‐activated zinc dust at 60°C for 15 min to reduce AAs to their respective aristolactams (ALs; Figure ) . After cooling to room temperature, 50 μL of internal standard, benz[ cd ]indol‐2(1 H )‐one (200 ng/mL), was spiked to the samples, which were vortex‐mixed and centrifuged at 13 800 g for 5 min prior to analysis using the LC/MS/MS method described below.…”
Section: Methodsmentioning
confidence: 99%
“…Since the 1990s, the use of AA‐containing herbs has been prohibited for preparing herbal medicines in many countries, including the USA . Despite the worldwide ban on the use of AA‐containing Aristolochia plants as traditional herbal medicine and in herbal remedies, it was estimated that over a hundred million people are potential victims of AA poisoning, due to the traditional practice of Chinese herbal medicine, the misuse of AA‐containing herbs and environmental exposure …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations